Ser é ser percebido- um exame de duas interpretações da justificação do esse est percipi na filosofia de George Berkeley - Siqueira, Jean Rodrigues (2005)
The aim of this dissertation is to examine two different interpretations concerning the justification of the necessity of the esse est percipi thesis in the philosophy of George Berkeley. According to one of them, the identification interpretation, what secures this justification is the philosopher s denial of any difference between the act and the object of perception. The defenders of this line of reasoning like Grave and Pitcher says that, as for Berkeley there is an identity between the act and the object of perception, the latter necessarily has to be thought to be in the mind , just like the act is. According to the other, the so-called inherence interpretation, what legitimates Berkeley s claim that perception is a necessary condition of the being of sensible things is his acceptance of the dictum that qualities must inhere in substances (the inherence principle). To the champions of this reading Allaire and Cummins, for example Berkeley s denial of material substance and his commitment to the inherence principle leaves the philosopher with the need to find an ontological support to the sensible qualities; as the only substance available in his ontology is the mind, then the qualities must exist in the mind , that is, their esse is percipi. As to the first interpretation, it will be shown that Berkeley never says that the distinction between the act and the object of perception is a bogus one, or that the act and the object of perception are identical; he only says that the object of perception cannot be dissociated from the act to which he is referred, nor thought to be a extra-mental entity. As to the second interpretation, it will be shown that while Berkeley believes that qualities depend on substances to exist, he doesn t conceives this dependence in terms of inherence. By showing that neither of these traditional explications of the internal necessity of the esse est percipi in Berkeley s philosophy is loyal to the spirit and the letter of his writings, this dissertation calls attention to the need of an alternative reading.